FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2014/2016 - Budi Santoso, 14.05.52.0086; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
This study is examines and analyze the effect of Return On Equity, Debt to Equity Ratio, Earning Per Share, dan Current Ratio of the bond rating on the property and real estate companies listed on the Indonesia Stock Exchange in the period 2014-2016.This study used purposive sampling method in sample selecction, the criteria for a sample of the property and real estate companies listed in Indonesia Stock Exchange (IDX)during the period 2014-2016. Based on these criteria, obtained a sample of 103 companies over a three-year observation period. Relationship and or influence between variables explainned by using multiple linear regression analysis method.The results showed that the variables Return On Equity and Debt to Equity Ratio had a significant positive effect on stock returns, the variable Earning Per Share had no significant negative effect on stock returns, and the variable Current Ratio had no significant positive effect on stock returns. Keywords: Return Saham, Return On Equity, Debt to Equity Ratio, Earning Per Share, dan Current Ratio.